Hong Kong SAR as a Financial Center for Asia : Trends and Implications - Unteroberdoerster, Olaf (IMF Working Papers; Working Paper ;, 2008)
We document Hong Kong SAR's evolving role as an international financial center in the Asia region, the importance of the growing special link with China as well as supply-side advantages, and outline the scope for future financial services growth. Hong Kong SAR has a long established track record as Asia's premier center for cross-border financial transactions. Further financial opening of China is likely to consolidate Hong Kong SAR's leading position as Asia's international financial center over the medium term. However, preserving Hong Kong SAR's first-mover advantage in the long-term calls for a development strategy that balances reaping the benefits from the special China role with the need to transcend into a truly international center in the long run.